Recovering Biblical Sensuousness - Thomas Ambooken (Journal of Dharma, 1976)
This volume is an attempt to discover some of the neglected aspects of the Biblical Religion. William Phipps sets out to show that, contra- ry to the opinions often held, the Bible does not emphasise the other- worldly at the expense of the natural. The goal of the authentic Chri- stian personality development is shown to be the dynamic harmoniz- ation and humanization of the supernatural and natural, in all of their reciprocal relationships.